(untitled) (Journal of actual problems of jurisprudence, 2018)
In article communication of legislative activity with social development and their interdependence is considered. Also in article the objective bases and subjective factors influencing lawmaking of the country on contents of laws, an essence of these factors, their value, need to consider them in the course of lawmaking, and also coherence of objective bases and subjective factors at the publication of laws reveal. Key words: law, legislative activity, law-making, state, public interests, objective bases, subjective factors, public relation, legal regulation, planning.